Structure-Based Design of Acetolactate Synthase From Bacillus licheniformis Improved Protein Stability Under Acidic Conditions - Zhao, Ting; Li, Yuan; Yuan, Siqi; Ye, Yang; Peng, Zhifu; Zhou, Rongqing; Liu, Jun (Frontiers in Microbiology, 2020)
The catabolic acetolactate synthase (cALS) plays a crucial role in the quality of liquor owing to its ability to catalyze the synthesis of the endogenous precursor product α-acetolactate of the aromatic compound tetramethylpyrazine (TTMP) and acetoin. However, the vulnerability of cALS to acidic conditions limits its application in the Chinese liquor brewing industry. Here we report the biochemical characterization of cALS from B. licheniformis T2 (BlALS) screened from Chinese liquor brewing microorganisms. BlALS showed optimal activity levels at pH 7.0, and the values of Km and Vmax were 28.07 μM and 13.24 mM·min-1, respectively. Through site-directed mutagenesis, we had improved the stability of BlALS under acidic conditions. Replacing the two basic residues of the BlALS with acidic mutations (N210D and H399D) significantly improved the acid tolerance of the enzyme with a prolonged half-life of 2.2 h (compared to the WT BlALS of 0.8 h) at pH 4.0. Base on the analysis of homologous modeling, we found that the positive charge area of the electrostatic potential on the protein surface and the number of hydrogen bonds near the active site had increased, which helped BlALSN210D-H399D to withstand the acidic environment and could extend its application in the food fermentation industry.